Historical background of Ben Cao Gang Mu (《本草纲目》 Compendium of Materia Medica) - Dongfang Yang; Xingliang Yang (Wolters Kluwer Health/LWW, 2019)
The compilation of Compendium of Materia Medica by Li Shizhen is the product of both his great dream of writing and years of diligent work and it was also all round related to the historical times when he lived. At that time, the appreciation from the Emperor, competitive publication of medical works by the state kings and the rapid developments in medicine in the Ming dynasty all contributed to the establishment of a solid foundation for the success of Compendium of Materia Medica. This paper explored the contributing factors of the great work from a perspective of the historical environment.